Analysis of Muslim Community Perspectives on Islamic-Based Primary Schools - Sarianto, Debi; Ayad, Nahid; Rahman, Ikhwan; Albizar, Albizar (Al-kayyis: Journal of Islamic Education, 2024)
Parents' interest in sending their sons and daughters to Integrated Islamic Elementary Schools is very high, even though the costs of studying there are quite high. Compared to general state schools, which are usually free (no fees), this research aims to find out and answer the question of why integrated Islamic primary schools are in great demand by the Indonesian Muslim community, especially parents. This research uses the method qualitative, using a case study approach. Research data was taken through in-depth interviews with five people, consisting of principals, teachers, and parents, at Integrated Islamic Primary Schools selected through Analysis Interactive Model Milles & Hubberman. This research shows that parents' interest in sending their sons and daughters to Integrated Islamic Primary Schools includes three factors: theological, sociological, and academic. i) Theological factors are views based on religious considerations. ii) Sociological factors related to views on the increasing image of Islamic schools in Indonesia. iii) Academic factors relate to the ability of integrated Islamic primary schools to achieve high academic achievements for both students and teachers. The results of this research can be used as information and initial data for subsequent researchers studying this problem in different contexts and issues.